2016
DOI: 10.1149/2.0761613jes
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al2O3in Porous Zirconia Electrolytes for NO Sensing

Abstract: The electrochemical behavior of NO sensors composed of a partially-stabilized Y 2 O 3 -ZrO 2 (PSZ) porous electrolyte with 0, 2, 3.8, 5 and 10 wt% Al 2 O 3 additions was investigated using the impedancemetric technique. The addition of Al 2 O 3 modified ionic transport within the electrolyte, and caused the electrode/electrolyte interfacial resistance to increase. NO sensors with a PSZ electrolyte containing 2 wt% Al 2 O 3 demonstrated greater sensitivity to NO under dry and humidified gas conditions, in compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Accumulation of various molecules at the electrode/electrolyte interface can also enable undesirable reactions to proceed leading to cross-sensitivity. The impact of water cross-sensitivity has been ambiguous as it can cause the NO x sensing response to increase or decrease [4][5][6]. Some studies suggest that the different behavior observed is related to the sensor materials, fabrication methods, and operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation of various molecules at the electrode/electrolyte interface can also enable undesirable reactions to proceed leading to cross-sensitivity. The impact of water cross-sensitivity has been ambiguous as it can cause the NO x sensing response to increase or decrease [4][5][6]. Some studies suggest that the different behavior observed is related to the sensor materials, fabrication methods, and operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The impedance describing the high-frequency data, Z HF , in the equivalent circuit model of FSZ composite electrolyte is described by the following complex equation [ 22 , 24 , 32 , 61 ]: where j = √−1, ω = 2πf, and f is the sensor operating frequency. The non-ideality factor, n, determines the fit of Q HF and represents the depressed semicircle nature of the arc in the porous electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…Among the limited studies relevant to sensing NO x, it has been reported that adding low amounts (i.e., 0.5–2 wt%) of Al 2 O 3 to YSZ removes SiO 2 impurities from grain boundaries, thereby facilitating ionic conductivity along the grain boundaries [ 20 , 21 ]. Porous composite electrolyte supported NO x sensors evaluated by Kharashi et al found that adding 2 wt% Al 2 O 3 to the partially stabilized zirconia (PSZ) electrolyte promoted greater NO x sensitivity compared to the non-composite PSZ supported sensors [ 22 ]. Increasing the Al 2 O 3 concentration beyond 2 wt% adversely impacted sensor sensitivity to NO as the insulating properties of Al 2 O 3 became apparent [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the elec-trochemical responses of the 50PSZ-50FSZ-based sensors indicated PSZ contributed to lower water cross-sensitivity, while FSZ promoted NO x sensitivity. Finally, sensors composed of the 50PSZ-50FSZ composite electrolyte demonstrated signiicant sensitivity to NO and low crosssensitivity to water with negligible temperature dependence [32][33][34][35].…”
mentioning
confidence: 98%